SARS-CoV-2 Specific Humoral Immune Responses after BNT162b2 Vaccination in Hospital Healthcare Workers - Golshani, Maryam; Svobodová, Ludmila Maffei; Štěpánek, Lubomír; Zeman, Jan; Nytrová, Petra; Posová, Helena; Petrásková, Petra; Novotná, Olga; Nováková, Michaela; Černý, Viktor; Beneš, Jiří; Kolářová, Libuše; et al. (Vaccines, 2022)
BACKGROUND: COVID-19 pandemic has led to a loss of human life in millions and devastating socio-economic consequences worldwide. So far, vaccination is the most effective long-term strategy to control and prevent severe COVID-19 disease. The aim of the current study was to evaluate the humoral immune responses raised against the BNT162b2 vaccine in hospital healthcare workers. METHODS: Total number of 173 healthcare workers enrolled in the study. Their blood samples were collected in three different time intervals after the second SARS-CoV-2 vaccination and evaluated by the ELISA method to detect anti-spike protein IgM and IgG antibodies. The baseline characteristics of all participants were collected using questionnaires and were evaluated for finding any significant data. RESULTS: Our results demonstrated that the levels of antibodies were higher in the young group (21-30 years old) and also among male participants. Moreover, the highest levels of antibodies were detected from the group that received the third shot vaccination. CONCLUSIONS: Our results indicate that age, gender and third-dose vaccination can affect the levels of humoral immune responses against the BNT162b2 vaccine in healthcare workers.
Keywords: BNT162b2; mRNA vaccine; antibody titer; SARS-CoV-2; ELISA; spike protein; COVID-19